Respostas
respondido por:
2
{-x -4y = 0
{3x +2y = 5 *(2)
{-x -4y = 0
{6x +4y = 10
5x ± 0y = 10
x = 10/5
x = 2
{-x -4y = 0
-2 -4y = 0
4y = -2
y = -0,5.
{3x +2y = 5 *(2)
{-x -4y = 0
{6x +4y = 10
5x ± 0y = 10
x = 10/5
x = 2
{-x -4y = 0
-2 -4y = 0
4y = -2
y = -0,5.
respondido por:
1
-x-4y=0 -> x= -4y -> x= -4(-1/2) x=4/2 x=2
3x+2y=5
3(-4y)+2y=5
-12y+2y=5
-10y=5
y= -5/10
y= -1/2
3x+2y=5
3(-4y)+2y=5
-12y+2y=5
-10y=5
y= -5/10
y= -1/2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás